The Potential Of Cinnamon (Cinnamomum Burmanni) Toothpaste as a Resistance To The Growth of the Streptococus Mutans Bacteria owth - Wahyu Jati Dyah Utami; Annisaa Sittatunnikmah; Sukini Sukini; Suwarsono Suwarsono; Yodong Yodong (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Introduction: A microorganism that plays an important role in dental caries is Streptococcus mutans. Dental caries can be prevented by brushing your teeth. The addition of antibacterial to toothpaste can reduce the number of caries-causing bacteria. Some anti-bacterial ingredients commonly added to toothpaste include fluorine, triclosan, and sodium monophosphate.Purpose: In this study, researchers wanted to develop an alternative toothpaste with cinnamon extract as an antibacterial ingredient. This research was conducted to formulate toothpaste with various concentrations of cinnamon extract 5%, 7.5%, and 10% and to determine the optimal concentration that can inhibit the growth of Streptococcus mutants bacteria.Method: The type of research conducted is experimental laboratories with a research design post-test only control group design. The toothpaste formulation is made with the active ingredient cinnamon extract with a concentration of 5%, 7.5%, and 10%. Cinnamon toothpaste was then tested on agar media which already contained Streptococcus mutans cultures. In addition, there is siwak herbal toothpaste as a positive control. Bacterial inhibition was analyzed statistically using the method one-way anova at the 95% confidence levelResults: research shows that cinnamon extract toothpaste with a concentration of 5%, 7.5%, 10%, and control+ has an average resistance of 11.5mm, 12mm, 12.5mm and 13mm. The results of data analysis by testanova show that p0.05. This shows that there are significant differences in the concentrations of the three cinnamon extracts. After obtaining the results One-Way Anova test significantly continued with the LSD test The results showed that there was no significant difference between the positive control and cinnamon toothpaste with a concentration of 10%, ρ=0.153. This shows that the inhibitory power of 10% cinnamon toothpaste is close to the positive control. This shows that the higher the concentration of cinnamon extract, the more antibacterial and bioactive content.